PEMBUATAN DATA BASE DAN SURAT OTOMATIS UNTUK MENINGKATKAN PELAYANAN KEPADA MASYARAKAT DI DESA KONCER DARUL AMAN KABUPATEN BONDOWOSO - Aimmah, Najwa Ziinatul; Harmansyah, Mochammad Taufiq; Dewi, Titik Tri Diana; Tobing, Diana Sulianti K.; Krishnabudi, Nyoman Gede (Fakultas Ekonomi dan Bisnis, 2024)
Abstract Effective and efficient data management is very important, especially for village governments whose task is to serve the community at the lowest level. Accurate and structured data makes it easier for villages to carry out various programs and administrative activities. Databases on sheets play a crucial role in managing data in villages, especially in organizing complex and diverse data. By applying sheets as a database, villages can integrate various types of information, ranging from population data, finances, to asset inventories. The application of technology in the form of automatic letter creation is a very relevant solution. Automatic letter generation allows villages to produce various types of letters quickly and accurately using provided templates.